(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The need to live in a community requires the provision of funds to finance the costs of that community, and taxation is considered legitimate. Because economic power is captured, as disposable income is reduced, taxation can trigger different taxpayer resistance modalities. Often, taxpayers intentionally and deliberately undertake certain activities that are in breach of tax regulations in order to reduce or completely default on their tax liability. Incriminating the most serious forms of illegal behavior of taxpayers as tax crimes is aimed at providing criminal protection of the fiscal system of the state. Against a wide range of highly profitable criminal activities, tax crimes are the focus of this work, because they directly affect the economic as well as national security of the state. The paper points the international and national criminal framework for combating money laundering as a form of organized crime. The authors has been analyzed and investigated case law in relation to reported money laundering offenses, court proceedings initiated (indictments) and convictions issued in the last five years. The jurisprudence testifies to the increasing frequency of committing this category of offenses, as well as to the extremely high profits generated by them. The profits gained in this way can be a source of "dirty money", but proving its origin in practice is difficult. An aggravating circumstance occurs when the illicitly acquired profits are integrated into legal cash flows. Difficulties of this kind can be avoided by closer and continuous cooperation between the judiciary and other competent authorities, which would result in an examination of the origin of money at the initial, investment stage when proof and prosecution are in some way feasible.